Aggressive familial ALS with unusual brain MRI and a SOD1 gene mutation - Blumen, Sergiu C.; Inzelberg, Rivka; Nisipeanu, Puiu; Carasso, Ralph L.; Oved, Daniel; Aizenstein, Orna; Drory, Vivian E.; Bergstrom, Christina; Andersen, Peter M. (Amyotrophic lateral sclerosis, 2010)
We studied two sisters with rapidly progressing ALS starting at the ages of 46 and 48 years and leading to death after 14 months. Both fulfilled the El Escorial criteria for definite ALS and had marked upper motor neuron (UMN) predominance. Brain MRI, on fluid attenuation recovery (FLAIR) mode, showed outstanding hyperintensities of the precentral gyrus, centrum semiovale, corona radiata and along the corticospinal pathways in the brainstem. Screening for the SOD1 gene disclosed, at codon 140, a base substitution of adenine for thymine (GGT>CCA) known as the A140A 'silent' mutation since it does not change the amino acid (alanine) encoded for at that position. The severe UMN involvement and the fast progression of the disease may correlate with the MRI findings. It is also possible that the A140A mutation is not incidental; the mutated mRNA might be cytotoxic.